The Acoustic Research in the Department of Architectural Science Ryerson University - Berardi, Umberto; Ramakrishnan, Ramani (Canadian Acoustics, 2016)
The building science laboratory in the Department of Architectural Science has capabilities to conduct research activities in the field of room acoustics and noise control. Four impedance tubes, with both two-microphone and three-microphone systems, are available to evaluate the absorption coefficient as well as a number of other material properties. A scale model wind tunnel is also available for source localization experiments. Detailed finite element modelling, through COMSOL, are used to predict acoustic performance of passive silencers, Helmholtz resonators as well as sound propagation in the available wind tunnels. Similarly, aero-acoustic simulations are also possible by using the software ACTRAN. Finally, auditorium and room acoustic researches are conducted through simulations as well as through in field measurements.